Chestnut tannins in broiler diets: performance, nutrient digestibility, and meat quality - Kobe Buyse (Elsevier, 2021)
ABSTRACT: In 2 broiler trials, the effects of chestnut tannins on performance and meat quality (trial 1), and digestion (trial 2) were evaluated. In both trials, Ross 308 broilers received one of 2 basal diets: one basal diet contained corn and soy as main feed ingredients, while the challenge basal diet contained wheat, palm oil, and rapeseed meal. The composition of the basal diets was chosen to assess the interaction between chestnut tannins and diet composition. To both basal diets, chestnut tannins were added at 3 doses: 0 mg/kg (T−), 500 mg/kg (T+), or 2,000 mg/kg (T++), resulting in a total of 6 treatments. In trial 1, both basal diets containing 2,000 mg/kg chestnut tannins lowered broiler performance in grower and finisher phases. A tannin dose of 500 mg/kg had no effect on performance in either basal diet. Corn-based diets resulted in lower meat pH compared to wheat diets. Further, addition of chestnut tannins resulted in increased meat pH, and caused proportionally a lower meat drip loss and shear force for both basal diets. During the digestibility study (trial 2), blood was also collected. None of the treatments affected digestibility or blood parameters (glucose, non-esterified fatty acids, and triacylglycerols). Malondialdehyde (MDA) was measured in plasma to assess antioxidative properties of chestnut tannins. In wheat diets, chestnut tannins significantly lowered plasma MDA demonstrating its antioxidative nature. Regarding gut health, crypt depth decreased proportionally with the dosage of chestnut tannins in both basal diets with significantly shallower crypts for the wheat diets compared to the corn diets. Relative intestinal growth was stimulated in the wheat diets proportionally to the tannin dose based on the larger relative gut length. In conclusion, chestnut tannins did not influence digestive metabolism, yet they lowered performance at higher doses regardless of feed ingredients used in the diet. Tannins positively affected meat quality and when added to wheat diets, intestinal growth was stimulated and the antioxidative status of the broilers improved.